LINGUOCULTURAL INTERPRETATION OF PLANT NAMES IN THE GERMAN TRANSLATION OF THE BABURNAMA - Abdurahmonova Dilrabokhon (Modern American Journals, 2025)
This paper explores the linguocultural interpretation of plant names (phytonyms) in the German translation of Baburnama, the famous memoir of the Mughal Emperor Zahiriddin Muhammad Babur. The study aims to analyze how linguistic and cultural meanings embedded in the plant-related vocabulary of the original text are conveyed or transformed in German translations. Through a comparative linguistic and cultural analysis of selected examples, the research reveals patterns of equivalence, adaptation, and cultural substitution. The findings show that the translator’s choices not only reflect linguistic competence but also cultural sensitivity, as plant names in Baburnama often carry symbolic, ecological, and ethnographic connotations. The article contributes to the broader field of translation studies by highlighting the intersection of lexicology, ethnolinguistics, and intercultural communication in historical literary translation.
Keywords: Baburnama, translation, phytonyms, linguocultural interpretation, German translation, ethnolinguistics, cultural equivalence.